(untitled) (diségno, 2022)
Graziano Mario Valenti’s book, entitled Di segno e Modello. Esplorazioni sulla forma libera fra disegno analogico e digitale, is undoubtedly an explicit example of experiences in research and didactics of representation. There is an air of experimentation in all the chapters of which the book is composed, since no unambiguous solutions are given to the many questions raised-an imperative present in the practice of every researcher-but at the same time an attempt is made to convey in the teaching experience-with the direct involvement of the students–the vocation to reflect on what is being done, beyond the simple technical application of established strategies of cognitive inquiry, so as to seek solutions that vary from time to time. The student, therefore, wears the clothes-often uncomfortable–of the careful experimenter who asks questions that, before him, few have asked. [read more]